Equimolar doses of hypertonic agents (saline or mannitol) in the treatment of intracranial hypertension after severe traumatic brain injury. Issue 38 (18th September 2020) - Huang, Xuecai; Yang, Lingling; Ye, Jinping; He, Shike; Wang, Baoping
Abstract: Background: Mannitol and hypertonic saline (HTS) are effective in reducing intracranial pressure (ICP) after severe traumatic brain injury (TBI). However, their efficacy on the ICP has not been evaluated rigorously. Objective: To evaluate the efficacy of repeated bolus dosing of HTS and mannitol in similar osmotic burdens to treat intracranial hypertension (ICH) in patients with severe TBI. Methods: The authors used an alternating treatment protocol to evaluate the efficacy of HTS with that of mannitol given for ICH episodes in patients treated for severe TBI at their hospital during 2017 to 2019. Doses of similar osmotic burdens (20% mannitol, 2 ml/kg, or 10% HTS, 0.63 ml/kg, administered as a bolus via a central venous catheter, infused over 15 minutes) were given alternately to the individual patient with severe TBI during ICH episodes. The choice of osmotic agents for the treatment of the initial ICH episode was determined on a randomized basis; osmotic agents were alternated for every subsequent ICH episode in each individual patient. intracranial pressure (ICP), mean arterial pressure (MAP), and cerebral perfusion pressure (CPP) were continuously monitored between the beginning of each osmotherapy and the return of ICP to 20 mm Hg. The duration of the effect of ICP reduction (between the beginning of osmotherapy and the return of ICP to 20 mm Hg), the maximum reduction of ICP and its time was recorded after each dose. Serum sodium and plasma osmolality were measured before, 0.5 hours and 3 hours after each dose. Adverse effects such as central pontine myelinolysis (CPM), severe fluctuations of serum sodium and plasma osmolality were assessed to evaluate the safety of repeated dosing of HTS and mannitol. Results: Eighty three patients with severe TBI were assessed, including 437 ICH episodes, receiving 236 doses of HTS and 221 doses of mannitol totally. There was no significant difference between equimolar HTS and mannitol boluses on the magnitude of ICP reduction, the duration of effect, and the time to lowest ICP achieved ( P > .05). The proportion of efficacious boluses was higher for HTS than for mannitol ( P = .016), as was the increase in serum sodium ( P = .038). The serum osmolality increased immediately after osmotherapy with a significant difference ( P = .017). No cases of CPM were detected. Conclusion: Repeat bolus dosing of 10% HTS and 20% mannitol appears to be significantly and similarly effective for treating ICH in patients with severe TBI. The proportion of efficacious doses of HTS on ICP reduction may be higher than mannitol.